Characterization of Alpha Mangostin Loaded-Mesoporous Silica Nanoparticle and the Impact on Dissolution and Physical Stability - Aulifa DL; Saepudin AH; Margaretha P; Khairinisa MA; Budiman A (Nanotechnology, Science and Applications)
Diah Lia Aulifa,1 Annisa Hafizhah Saepudin,1 Priskila Margaretha,1 Miski Aghnia Khairinisa,2 Arif Budiman3 1Department of Pharmaceutical Analysis and Medicinal Chemistry, Faculty of Pharmacy, Padjadjaran University, Sumedang, 45363, Indonesia; 2Department of Pharmacology and Clinical Pharmacy, Faculty of Pharmacy, Universitas Padjadjaran, Sumedang, 45363, Indonesia; 3Department of Pharmaceutics and Pharmaceutical Technology, Faculty of Pharmacy, Universitas Padjadjaran, Sumedang, 45363, IndonesiaCorrespondence: Diah Lia Aulifa, Department of Pharmaceutical Analysis and Medicinal Chemistry, Faculty of Pharmacy, Universitas Padjadjaran, Jl. Raya Bandung-Sumedang Km. 21, Bandung, 45363, Indonesia, Email diah.lia@unpad.ac.idPurpose: Improving drug solubility is crucial in formulating poorly water-soluble drugs, especially for oral administration. The incorporation of drugs into mesoporous silica nanoparticles (MSN) is widely used in the pharmaceutical industry to improve physical stability and solubility. Therefore, this study aimed to elucidate the mechanism of poorly water-soluble drugs within MSN, as well as evaluate the impact on the dissolution and physical stability.Methods: Alpha mangostin (AM) was adopted as a model of a poorly water-soluble drug, while MSN with the pore size of 45 Å (MSN45) and 120 Å (MSN120) were used as Mesoporous materials. AM-loaded MSN (AM/MSN45 and AM/MSN120) was prepared by solvent evaporation method.Results: The amorphization of AM/MSN45 and AM/MSN120 was confirmed by the halo pattern observed in the powder X-ray diffraction pattern and the absence of the melting peak and the glass transition of AM in the DSC curves. This signified the successful incorporation of AM into MSN. FT-IR measurements suggested the formation of hydrogen bond interaction between the carbonyl group of AM and the silica surface of MSN. In the dissolution test, the presence of the AM within MSN improved the dissolution rate and generated the supersaturation of AM. However, the difference of pores size of MSN could affect the dissolution profile of AM within MSN. Additionally, it retained the X-ray halo patterns after 30 d of storage at 25 oC and 0% RH.Conclusion: In conclusion, AM-loaded mesoporous silica significantly improved the dissolution and physical stability.Keywords: mesoporous silica, alpha mangostin, amorphization, dissolution, physical stability